Surgical treatment of fractures of the ankylosed spine - Silva, MAC (2020)
Objective: We aim to identify retrospectively surgically treated patients with an ankylosed spine who sustained a vertebral fracture. Our goal is to evaluate the main outcomes and complications. Methods: We selected patients through the database of surgical interventions in the setting of fractures of an ankylosed spine segment between January 1st 2008 and June 30th 2018. We collected data from digital medical records. The parameters analyzed include hospital length of stay, Intensive Care Unit (ICU) admission, perioperative and postoperative complications as well as neurological evolution. Results: Fractures occurred in 14 patients with ankylosing spondylitis (82%) and 3 patients with diffuse idiopathic skeletal hyperostosis (18%). All patients were male and the mean age was 69 years. Fourteen fractures occurred after minor trauma (83%), of which 11 were due to falls from standing height or lower (65%). The cervical spine represents the majority of the levels involved (65%). Seven patients were admitted to the ICU (41%) and 11 suffered neurological damage. There was improvement of neurological status in less than 50% and there were high percentages of post-operative complications. Conclusion: Patients with ankylosed spine diseases are at higher risk for vertebral fracture, even after minor trauma, and these are located predominantly in the cervical spine. The surgical treatment of these conditions is effective as it allows improvement of the patient's neurological status. However, they still present higher morbidity and mortality, as well as increased post-op complications. Prevention of falls may drastically change patients' outcome, neurological function and independence in activities of daily living. Level of evidence IV; A case series therapeutic study.